Development of Pectin and Poly(vinyl alcohol)-Based Active Packaging Enriched with Itaconic Acid and Apple Pomace-Derived Antioxidants - Bernadette-Emőke Teleky; Laura Mitrea; Diana Plamada; Silvia Amalia Nemes; Lavinia-Florina Călinoiu; Mihaela Stefana Pascuta; Rodica-Anita Varvara; Katalin Szabo; Patricia Vajda; Cristian Szekely; Gheorghe-Adrian Martău; Simon Elemer; et al. (MDPI AG, 2022)
The production of active and biodegradable packaging materials is an emerging and efficient alternative to plastic packaging materials. By combining poly(vinyl alcohol) (PVA), pectin, and itaconic acid (IA), biodegradable and water-soluble packaging materials can be obtained that can also increase the shelf-life and quality of foodstuff. In the present study, the generated film-forming solutions were enriched with organic or phenolic extracts from apple by-products (apple pomace). These extracts possess an efficient antioxidant activity of 9.70 ± 0.08, and 78.61 ± 0.24 μM Trolox/100 g fresh weight, respectively. Furthermore, the lyophilization of these by-products increased the extract's organic and phenolic content and the antioxidant activity to 67.45 ± 0.28 and 166.69 ± 0.47 μM Trolox/100 g fresh weight, respectively. These extracts influence the physical-chemical properties of the biofilm solutions by facilitating the polymerization process and thus positively influencing their viscosity. The resulting biofilms presented low water vapor permeability and reduced solubility in water. Adding IA and organic/phenolic compounds facilitates the resistance against intrinsic and extrinsic factors; therefore, they might be applicable in the food industry.